Evaluación de la fluctuación poblacional de artrópodos en el cultivo de arroz (oryza sativa l.) Variedad capirona, bajo el sistema de trasplante en el valle del Bajo Mayo, San Martín - Ríos Romero, Ronal (2003)
This research development between March-April 2003 in order to determine the population fluctuation (Arthropods) insects in rice cultivation, Variety Capirona from transplantation to harvest, in the Core Sector Valle del Bajo Mayo . This experiment was carried out on the estate of Lord Michael Tello Alexandria, located in the Cacatachi District, province and region of San Martin, geographically located at 6 ° 29 'South Latitude. 76 ° 27 'west longitude at an altitude of 295 m.s.n.m.m, evaluations were made with entomological net and directly from him same floor in a total area of ​​4 hectares parceled into four sectors of one hectare for sampling. The results indicate that among herbivorous insects captured with entomological network are:. Tagosodes sp, Ussothoptros sp, Oebslus sp, Rupela albinella, Chironomidae and Cicadelidae, while among natural enemies were.. Arachnids, syrphidae, odonata and ícheumonidae. In the evaluations we have phytophagous plants: Usshoroptrus Spodoptera sp and sp and between natural enemies entomopathogenic fungi, predacious bugs, Allograpta sp, arachnids, lampiridos and spotted lady beetle..